Human–Landscape Interactions during the Early and High Medieval Period in Central Spain Based on New Estimates of Sediment Yield from the Melque Agricultural Complex. Issue 2 (18th July 2016) - Ortega, Raúl; Vanacker, Veerle; Sanjurjo‐Sánchez, Jorge; Miralles, Isabel
Abstract : An agrosilvopastoral system and millennium of human occupation make Santa Maria de Melque an important archaeological site in Europe. Previous archaeological work mainly focused on ceramics and wooden structural elements of a church and anthracological, palynological, and paleocarpological analyses of sediments around a rural monastery. In this paper, we extend the geoarchaeological work to dams that were constructed nearby, applying innovative techniques such as optically stimulated luminescence (OSL) dating and seismic refraction to help understand human–landscape interactions. Our OSL dating of dams and reservoir sediments provide a first detailed chronological framework for historical water storage in Central Spain. In Melque, the four dams were built consecutively during phases of Christian occupation, thereby assuring water availability to support agrosilvopastoral activities. The maximum splendor of the rural complex occurred during Phase III (Christian occupation, 12th–16th centuries A.D.). Dam construction was an integral part of the agricultural production system, and the reservoirs were effective as water harvesting systems in support of irrigated agriculture from the 7th to 16th centuries A.D. during the Early and High Medieval occupation of the site.